Who and how should participate in health care priority setting? evidence from a Portuguese survey - Botelho, Anabela (2011)
This article provides highlights of the evolution of the health care rationing debate towards a more transparent and open approach involving public participation. Discretionary models that have dominated health sector decision-making are being questioned by different sectors of society. Using data from 442 college students, we explore public’s views on its involvement in health care rationing decisions. Findings suggest that although citizens wish to be consulted, they believe doctors should play the most important role on the rationing decisions. Nonetheless, the confidence in doctors is not independent of the criteria used to support their decisions.